2019
DOI: 10.1007/s40265-019-01107-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Profiles on Subjective and Objective Adherence Measures in Patients Prescribed Antidepressants

Abstract: Objective A recurrent observation is that associations between self-reported and objective medication adherence measures are often weak to moderate. Our aim was therefore to identify patients with different profiles on self-reported and objective adherence measures. Study Design and Setting This was an observational study of 221 community pharmacy patients who were dispensed antidepressants. Adherence profiles were estimated with Latent Profile Analysis (LPA) using data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A study done as UK Defeat Depression Campaign indicated that the effective antidepressant drug therapy, the treatment duration should not be less than four consecutive months, but in their study, they found only 31% of patients adherence to the fourth month (SSRIs: fluoxetine: 31%; paroxetine: 30%; sertraline: 24%) 25,29 . This study showed that the higher rate of adherence (17%) is in males with the P-value of 0.324, and it was also observed that patients who were never married had a higher percentage of adherence (18%).…”
Section: Discussionmentioning
confidence: 99%
“…A study done as UK Defeat Depression Campaign indicated that the effective antidepressant drug therapy, the treatment duration should not be less than four consecutive months, but in their study, they found only 31% of patients adherence to the fourth month (SSRIs: fluoxetine: 31%; paroxetine: 30%; sertraline: 24%) 25,29 . This study showed that the higher rate of adherence (17%) is in males with the P-value of 0.324, and it was also observed that patients who were never married had a higher percentage of adherence (18%).…”
Section: Discussionmentioning
confidence: 99%
“…Digital health interventions are interventions delivered through digital technologies such as text messages, phone calls, websites, and apps. Previous studies ( 28 , 29 ) have shown that results between subjective and objective measures of adherence are not always consistent, and the study by Cross et al ( 14 ) categorized adherence measures into subjective and objective measures. Therefore, the primary outcomes assessed adherence to oral iron supplementation (with objective and/or subjective measure) and tablets consumption.…”
Section: Methodsmentioning
confidence: 99%
“…24 To provide the most informed patient care, providers should ideally verify medication adherence with objective measures. 25 Accurate medication adherence data can support providers when making clinical decisions (eg, treatment modification for patients whose symptoms are not well controlled) 20,26 and help identify individuals who need additional support with adherence. 27 Several advances in technology and medication formulations have emerged to improve the accuracy of determining medication adherence.…”
Section: Introductionmentioning
confidence: 99%